Characterization and Classification of Teak-Supporting Soils in Seoni District of Madhya Pradesh - Choudhari, Pushpajeet L.; Prasad, Jagdish; Gurav, Priya (Indian Forester, 2019)
Black and associated red soils (5 pedons) occurring on different landforms having developed on basalt under teak in Seoni district of Madhya Pradesh were studied for their morphological, physical and chemical properties. The soils were very shallow (P1, 13 cm) to very deep (P4, 158 cm). Pedon 1, 3, 4 and 5 had their colour in hue 5YR or redder barring P2 but their texture is dominantly clay. In general, the organic carbon decreased with depth. The pedon 1 was classified as Entisols whereas, pedon 3 (Parasia) classified as an Inceptisols. The other pedon 2 (Parasia), 4 (Mohgaon) and 5 (Gondatola)were classified as Alfisols. Growth of teak was better in shallow soils developed from weathered basalt as compared to deep lateritic soil. The variation in the growth, quality and distribution of teak is mostly dictated by soil-site characteristics.